Phonemic restoration in developmental dyslexia - Del Tufo, Stephanie N.; Myers, Emily B. (Frontiers in Neuroscience, 2014)
The comprehension of fluent speech in one's native language requires that listeners integrate the detailed acoustic-phonetic information available in the sound signal with linguistic knowledge. This interplay is especially apparent in the phoneme restoration effect, a phenomenon in which a missing phoneme is “restored” via the influence of top-down information from the lexicon and through bottom-up acoustic processing. Developmental dyslexia is a disorder characterized by an inability to read at the level of one's peers without any clear failure due to environmental influences. In the current study we utilized the phonemic restoration illusion paradigm to examine individual differences in phonemic restoration across a range of reading ability, from very good to dyslexic readers. Results demonstrate that restoration occurs less in those who have high scores on measures of phonological processing. Based on these results, we suggest that the processing or representation of acoustic detail may not be as reliable in poor and dyslexic readers, with the result that lexical information is more likely to override acoustic properties of the stimuli. This pattern of increased restoration could result from a failure of perceptual tuning, in which unstable representations of speech sounds result in the acceptance of non-speech sounds as speech. An additional or alternative theory is that degraded or impaired phonological processing at the speech sound level may reflect architecture that is overly plastic and consequently fails to stabilize appropriately for speech sound representations. Therefore, the inability to separate speech and noise may result as a deficit in separating noise from the acoustic signal.